Sintesis Selulosa Asetat Dari Limbah Sabut Siwalan (Borassus Flabellifer L) dengan Metode Emil Heuser - Rohman, Irsyad Zaki; Natasya Salsabila Putri Djunaidy; Ely Kurniati (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Acetate cellulose is a valuable biopolymer with a variety of industrial applications, ranging from textile fibres to biodegradable plastic films. Using local biomass waste, such as palm fibre (Borassus flabellifer L.), to produce acetate cellulose offers a sustainable way to reduce dependence on imported raw materials and address organic waste issues. This study aims to synthesise cellulose acetate from palm fibre waste using the Emil Heuser method, optimising the acetylation reaction parameters to produce a product with maximum acetyl content. Synthesis was achieved by varying the volume of glacial acetic acid (30–90 ml) and the acetylation time (5–25 minutes). The acetyl content was measured using the ASTM D-871 titration method and the presence of functional groups was confirmed by FTIR spectroscopy. The highest acetyl content, 34.71%, was obtained under the optimal conditions of 90 ml of glacial acetic acid and an acetylation time of 15 minutes. FTIR analysis confirmed the presence of the characteristic C=O (1,740 cm⁻¹) and C–O (1,240 cm⁻¹) functional groups, indicating that the acetylation reaction had successfully occurred on the cellulose chain. While the resulting product was classified as cellulose monoacetate and did not meet the SNI commercial standard for cellulose triacetate, these results demonstrate the significant potential of palm fibre as a local, sustainable natural resource for producing cellulose acetate with further optimisation.